When Do Board Interlocks Matter? The Adoption of Share Buyback and Stock Option Pay in Japanese Firms - YOSHIKAWA, Toru (Institutional Knowledge at Singapore Management University, 2012)
This study examines the adoption of stock buyback and executive stock option compensation in Japanese firms. We investigate whether the presence of interlocking directors who sit on boards of other firms that adopted those practices is related to the adoption of the same practices by the focal firm. We also examine whether there are any differences in the effects of such board interlocks between family-controlled firms and non family-controlled firms. Our findings show that the presence of interlocking directors is significantly related to the adoptions. We also found that while the effect of such directors on the adoption of a stock buyback plan is stronger for non family-controlled firms, the effect on the adoption of a stock option pay is stronger for family-controlled firms.